2019
DOI: 10.1111/ijsa.12240
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in employee selection: The development of a gamified assessment

Abstract: Gamification has attracted increased attention among organizations and human resource professionals recently, as a novel and promising concept for attracting and selecting prospective employees. In the current study, we explore the construct validity of a new gamified assessment method in employee selection that we developed following the situational judgement test (SJT) methodology. Our findings support the applicability of game elements into a traditional form of assessment built to assess candidates' soft s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 59 publications
(98 reference statements)
2
81
0
7
Order By: Relevance
“…The studies [53]- [55] have used points to motivate the users. A point has been assigned to the user against each completed task.…”
Section: F Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies [53]- [55] have used points to motivate the users. A point has been assigned to the user against each completed task.…”
Section: F Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
“…The studies [26], [28], [40], [49] focused on defining how gamification and different gaming elements work to trigger the user motivational mechanism. Moreover, the studies [55], [29] presented a game-based solution to recruit and retain blood donors. The resolution was offered by considering how gamification affects behavior change.…”
Section: F Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
“…On the one hand, they need to look for, recruit and select employees who have the potential to adapt to the incoming change / challenge and progress in its context. On the other hand, they raise possibilities for using new technologies to make their work more efficient (Georgiou et al, 2019;Widhiarso et al, 2019). The survey showed that the human resources departments in the selection of employees try to comply with the established standards, focusing on both external and internal labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous scholars have stressed the importance of designing games through iterative approximation and continuous improvement (e.g. Georgiou et al, 2019;Ivan et al, 2019). Hence, most researchers working in the area of gamification in HRM agree that gathering feedback on gamification environments from as many individual employees as possible, and adapting the design likewise ensures an everincreasing effectiveness of the use of gamification (e.g.…”
Section: Designing Gamification In Hrmmentioning
confidence: 99%